Pettitt and Bayesian Change Point Detcetions in The Price of Kerosene in The Southwestern Region of Nigeria - Adepoju, Adedayo A.; Oludunni , Anihunlopo A; Ogundunmade, Tayo P. (International Journal of Data Science, 2022)
Kerosene is known to be one of the useful substances in crude oil. It is considered to be a useful household substance. It is a combustible hydrocarbon liquid widely used as fuel in industry and households. Over the years, it has been shown that there is an upward trend in the price of kerosene which has affected its use negatively. It would be of interest to investigate the change points in the price of kerosene in the six states of the southwestern region of Nigeria between 2015 and 2021. Mann Kendall trend test was used to determine the trends in the data. The Mann Kendall trend analysis showed a significant upward trend with their p-values less than 0.05 for all the States. Furthermore, Bayesian and Pettitt approaches were employed to detect change points in the price of Kerosene in the six states (Ekiti, Lagos, Ogun, Ondo, Osun, and Oyo) of the southwestern region of Nigeria. The Pettitt method showed a single shift in each of the States while the Bayesian approach showed multiple shifts in each State. Both methods give the change point with dates while the Bayesian also provides the posterior means for the change points.